Evaluation of linear dimensional accuracy of hard chairside and laboratory heat cure reline resins at different time intervals after processing - Shivsagar Tewary; Karuna G Pawashe (Wolters Kluwer Medknow Publications, 2014)
Context: Relining with heat cure denture base resin is time-consuming and the patient has to remain without dentures within this period. Recently, some autopolymerizing resins marketed as hard chairside reline systems with low exothermic heat allow the dentists to reline prosthesis directly in the mouth. However, the decision to use these materials must be based on physical properties such as dimensional accuracy that directly influences the accuracy of fit of the denture base. Aim: The aim was to compare the linear dimensional changes of two hard chairside reline resins with two laboratory heat cure resins at 3 times intervals after processing. Settings and Design: A stainless steel split mold (International Organization for Standardization 1567) was used for sample fabrication. Five measurements of the reference dimensions (AB and CD) were measured directly from the mold and the samples with a profile projector, and mean difference were calculated. Subjects and Methods: Forty samples were fabricated by incorporating the split mold into first pour of denture flasks and packing each of the chairside reline resins ("Kooliner" and "Ufi Gel Hard") and laboratory heat cure resins ("Dental Products of India Heat Cure" and "Trevalon"). The mean difference in dimensional change at 3 times intervals (0 h, 4 days and 2 months) were calculated and subjected to statistical analysis. Statistical Analysis Used: One-way ANOVA, RMANOVA and post hoc Tukey's tests. Results: All resins showed different levels of significant shrinkage (P < 0.001) after processing (T 0 ) ranging from −0.128 to −0.310 mm. After 4 days (T 1 ), there was significant shrinkage (P < 0.001) ranging from −0.168 to −0.296 mm. After 2 months (T 2 ), there was again significant shrinkage (P < 0.001) ranging from −0.018 to −0.216 mm. Chairside reline resins showed less dimensional shrinkage at each time interval than the laboratory heat cure resins. Conclusions: Hard chairside resins are dimensionally accurate than the laboratory heat cure resins.